A Simplified Displacement Spectrum Model Based on Recent Digital Strong-Motion Data. Issue 6 (26th April 2023) - Chen, Longwei; Wu, Xiaoyang; Guo, Tingting
ABSTRACT: Displacement spectrum is an essential aspect in displacement-based seismic design (DBSD) philosophy that, comparing to force-based, describes in a more explicit way the structural response and the damage. To better apply DBSD, the displacement spectrum model in period ranging up to 15 s is rephrased using recent high-quality digital strong motion data worldwide, particularly from China territory. After systematical analysis conducted of the influence factors as magnitude, distance, and site conditions on displacement spectrum, it is found that magnitude played a more predominant role in characterizing displacement spectrum that is normalized by peak ground-motion displacement than site conditions and distance. A simplified magnitude-scaled model consisting of four straight line segments constrained by three corner periods and their corresponding amplitudes is proposed to model the normalized displacement spectrum. Comparison with seismic data and the published models verifies the applicability of the proposed model especially for strong earthquakes. Residual analysis indicates the simplified model satisfactorily matches the records with respect to magnitude and distance but the variability of model prediction slightly tends to grow as magnitude and distance increase.